A constituição do enunciado nas provas do ENEM e do ENADE: uma análise dos aspectos semiológicos da relação língua-imagem sob a ótica dos estudos do discurso - Santos, Jocenilson Ribeiro dos (2011)
This research was developed into studies of discourse, which centrality is defined from the analysis of the mechanisms of enunciation institution in exams of Brazilian evaluation in order to study the relation language-image. The corpus of analysis is constituted by exams of Exame Nacional do Ensino Médio (ENEM) and Exame Nacional de Desempenho dos Estudantes (ENADE) in the editions of the years between 2004 and 2009, that means 7 exams of ENEM and 6 of ENADE. Before defining this temporal cutting, we have studied the six editions of ENEM that happened before 2004 in order to know the operation of the exams during the years. The general goal of this research was to understand that manners of evaluation of linguistic-discursive ability, having in mind the relation between language and the images in the production of sense presented in national systems of evaluation in High School and graduation by the two exams here evidenced. Our specific goals are: a) to analyze the relation established between the language and the image(s) presented in evaluative questions of ENEM and ENADE in the chosen period; b) to identify the theoretical assumptions involved in questions of this modality; c) to study the frequency and regularity of questions that present multimodal texts in the 12 editions of ENEM and in the 6 of ENADE; and d) to evaluate the relevance of the proposition of analysis from the theoretical frameworks of studies of discourse. It has been working as theoretical-analytical foundations the contributions based on the theory of Discourse Analysis of French filiation founded by Michel Pêcheux and his group, in the discursive formulations of Jean-Jacques Courtine and on the contributions of Michel Foucault for the discourse theory. We also bring the reflections of Émile Benveniste and, especially, of Roland Barthes about language from the semiological point of view in order to study the production of sense on imagery and mixed language. There are present on our work the notions of utterance, discourse, file, discursive memory, interdiscourse and historical semiology through which we developed methodologically the analysis. The corpus was basically organized according to three criteria: the coincidence in 2004 of the ENADE institution that would replace the old provão with the institution of PROUNI; the rise of number of images in the exams of ENEM; and the highlights of both exams that presented the image as the object of reading and comprehension that would be the responsible by the evaluation of student/candidate. The study brings three analytical ways: a) one in which we conducted a survey of exams, organizing the corpus, classifying the questions and observing the possible theories that were around the evaluation of those exams; b) another one showing the theory that has language, image or both correlated as object of study; and c) the analysis from the theoretical assumptions of discourse in order to study the mixed text as discourses materializations. We can present as findings some results: in the last Five years, there was a progressive attention to the imagery text in the evaluation systems that we are studying; in some occasions, the image is not only a mere flavor or didactical text, it is the object of interpretation; there is not a theory that is dedicated to reading and comprehending the image, which becomes a responsibility of the goals of the question to present a theory that often turns to verbal text or to them/content, making the image not an object of analysis, but as materialization or vehicle of a content that serves the analysis students.